Penggunaan E- Modul Berbasis Pendekatan Contextual Teaching and Learning (CTL) : Analisis Bibliometrik (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
A number of studies have discussed the development and implementation of e-modules based on the Contextual Teaching and Learning (CTL) approach at various levels of education. However, there is no study that systematically reviews and maps the development of research in this field. This study aims to provide a bibliometric overview of the development of studies on the use of CTL-based e-modules. A total of 13 scientific articles published in the period 2015 to 2025 were analyzed, with data obtained from Google Scholar using Publish or Perish software. The analysis was carried out descriptively and bibliometrically with the help of VOSviewer to visualize growth trends and thematic maps of the topics studied. This research focuses on two main aspects, namely: (a) the growth trajectory of studies related to the use of CTL-based e-modules; and (b) mapping the most researched themes and main topics. Results show a significant increase in interest since 2020, with the focus shifting from the introduction of CTL concepts towards the development, validation, and implementation of e-modules in learning. Visualization with VOSviewer also shows contextual teaching, e-module, and student as the dominant keywords in recent research. This finding is expected to be an initial reference for further research in this area.